Differences in learning strategies applied during listening comprehension among students aged 12-13 in a monolingual and multilingual environment in Transcarpathia - Siladi Vasyl; Szilágyi László; Сіладі Василь (ГО «Південна фундація педагогіки», 2021)
Abstract. Nowadays, it has become vital for high school students to strive for a higher level of foreign language skills. Nothing proves this, such as the fact that Transcarpathian, graduate students have to take a language exam in order to obtain a degree abroad, not to mention the advanced level exams introduced in Ukraine thirteen years ago.
Keywords: language learning; strategies; listening comprehension; monolingual; multilingual